2015
DOI: 10.4155/fmc.15.168
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Bicyclic Inhibitors Against Menaquinone Biosynthesis

Abstract: Introduction: Menaquinone is used for transporting electrons and is essential for the aerobic and anaerobic respiratory systems of all pathogens and prokaryotes. Many Gram-positive bacteria use only menaquinone in the electron transport system. Thus, menaquinone biosynthesis is a potential target for the development of inhibitors against bacteria including drug-resistant pathogens. Results: After modeling, synthesis and in vitro testing, we determined that 7-methoxy-2-naphthol-based inhibitors targeted the Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…16 Interestingly, not all of the enzymes have had signicant investigation into potential inhibitors. [18][19][20][21][22][23][24][25][26] To date the most promising results have come from inhibitors targeting the enzymes further downstream of the synthesis pathway. Major inhibitors that have been discovered to date will be reviewed in this article.…”
Section: Bacterial Synthesis Of Menaquinonementioning
confidence: 99%
“…16 Interestingly, not all of the enzymes have had signicant investigation into potential inhibitors. [18][19][20][21][22][23][24][25][26] To date the most promising results have come from inhibitors targeting the enzymes further downstream of the synthesis pathway. Major inhibitors that have been discovered to date will be reviewed in this article.…”
Section: Bacterial Synthesis Of Menaquinonementioning
confidence: 99%
“…Thus, an urgent need exists for simplified, long-acting, and effective regimens to treat HIV and M. tuberculosis coinfection (5). …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that MenA inhibitors possessing a simple, chemical structural backbone of 7-methoxy naphthalene are highly active against Gram-positive bacteria with low micromolar MIC and IC 50 values (compound 1 and 2 in Fig. 2)6. Here, we synthesized novel compounds to explore structure-activity relationships (compounds 3 to 7 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that compound 1 and 2 exhibited inhibition of both M.tb and MenA enzyme activity with IC 50 values of 6 and 5 μg/mL, respectively6. We synthesized long chain compounds with different functionalities to improve activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation